Physical and physiological profile of elite Iranian karate athletes - Faraji, H.; Nikookheslat, D.; Fatollahi, S.; Alizadeh, M. (International Journal of Applied Exercise Physiology, 2016)
No study to date, has investigated the physiologic and anthropometric of Iranian elite Karatekas profile. Forty men internationally ranked karatekas in kumite field took part in this study. They were selected for national camp for participation in world karate championships in Germany 2014. The anthropometric and physiological profiles were measured. The major results were as follows: body height (177.9±6.20 kg), weight (72.8±9.98 cm), BMI (23.2±2.36 kg/m2), fat mass (9.5±2.47 kg), lean body mass (64.1±8.89 kg), percentage of body fat (12.9±2.36), sitting height (95.1±4.21 cm), arm span (180.5±7.87 cm), sit and reach (38.7±5.71 cm), pull up (15.7±8.37 rep), shuttle run 4×9 m (8.4±0.28 sec), 40-yd sprint (5.0±0.16 sec), vertical jump Sargent (56.6±8.14 cm), standing broad jump (151.1±13.90 cm), peak power (957.5±164.11 W), anaerobic threshold (165.5±8.05 HR pm) and visual reaction time (378.8±63.82 ms). Significant correlations occurred between peak power with weight, BMI, height, lean body mass, arm span and sitting height (r = 0.75, 0.70, 0.53, 0.77, 0.44, and 0.63, respectively). Also, both arm span and height was negatively correlated to standing broad jump results (r= -0.41 and -0.34, respectively) (p< 0.05).